Glutathione sebagai pemutih kulit - Vira Katya Aurelia (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
GSH is one of the compounds that inhibits melanin production by inhibiting tyrosinase activity. Antimelanogenic properties of glutathione have resulted in doctors often giving it as a "miracle" medicine for skin lightening and treatment of hyperpigmentation, especially in ethnic populations with darker skin tones. However, its uncontrolled use, especially as a parenteral formulation, seems unjustified, given the lack of research in supporting this theory. Although there are mechanisms that inhibit the process of melanogenesis by considering the side effects in the form of impaired liver function. Its safety as an intravenous drug is also questionable. The use of Gluthatione as a skin lightening agent, either topically, orally, or intravenously shows mixed results in an enlightening effect. Further research must be carried out to ensure the safe use of this substance, some studies report that oral use shows better effectiveness than topical or intravenous, but the side effects that are also dangerous such as impaired liver function